2019
DOI: 10.3889/oamjms.2019.224
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Molar Incisor Hypomineralization among School Children Aged 9 to 12 Years in Virajpet, Karnataka, India

Abstract: BACKGROUND: The molar incisor hypomineralization (MIH) is defined as a qualitative defect of the enamel characterised by the progressive and simultaneous hypomineralization of the enamel structure of the first permanent molars which is of systemic origin, which may be associated frequently with incisors. Although the reported prevalence of MIH ranges from 2.4% to 40.2% worldwide, very little data is available from India. AIM: To determine the prevalence of molar incisor hypomineralization among school ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…The evidence that MIH frequency varies across the world [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] is supported by the results found in the present study. The association found in the Turkish population was different from the results obtained in the cohorts from Brazil, which indeed indicates that genetic factors contributing to the MIH phenotype may vary depending on geographic origin.…”
Section: Plos Onesupporting
confidence: 82%
See 1 more Smart Citation
“…The evidence that MIH frequency varies across the world [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] is supported by the results found in the present study. The association found in the Turkish population was different from the results obtained in the cohorts from Brazil, which indeed indicates that genetic factors contributing to the MIH phenotype may vary depending on geographic origin.…”
Section: Plos Onesupporting
confidence: 82%
“…These asymmetrical lesions affect the first permanent molars, usually with the permanent incisors [4], and more recently MIH has been reported to affect canines too [5]. Prevalence of MIH varies but has been consistently reported to range between 1% and 35% in all parts of the world, with most reported frequencies around 12% [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Davenport et al, in pilot research conducted in the USA, assessed the frequency of prevalence of MIH at 9.6% [ 31 ]. Moreover, a significantly higher prevalence of MIH was observed by Wainuiomata (14.9%) [ 32 ] in India—13.12% [ 33 ], Dubai—27.2% [ 34 ], Saudi Arabia—15.2% [ 35 ], and Lebanon—26.7 % [ 36 ]. To establish the accurate frequency of prevalence of MIH in Poland, thorough research must be carried out in Upper Silesia as well as other parts of Poland.…”
Section: Discussionmentioning
confidence: 99%
“…9 On the contrary, Rai PM et al reported a prevalence of 13.2%. 10 The age range taken in the present study of 8-12 years is recommended by the EAPD. In the present study a statistical difference was observed between females and males (p=0.03), which is in disagreement to Rai PM et al 10 A meta-analysis by Lopez et al also confirmed that MIH was not not sex-related and females and males presented a non-significant difference as per results.…”
Section: Discussionmentioning
confidence: 99%
“…10 The age range taken in the present study of 8-12 years is recommended by the EAPD. In the present study a statistical difference was observed between females and males (p=0.03), which is in disagreement to Rai PM et al 10 A meta-analysis by Lopez et al also confirmed that MIH was not not sex-related and females and males presented a non-significant difference as per results. 11 In the present study, a significant difference was observed regarding the prevalence of MIH between the maxillary teeth compared to the mandibular teeth (p=0,02), which is in disagreement with Yannam SD et al 8 and Jalevik et al…”
Section: Discussionmentioning
confidence: 99%